PENGARUH RASIO PROFITABILITAS DAN LIKUIDITASTERHADAP KEBIJAKAN DIVIDEN PADA PTUNILEVER INDONESIA TBKPERIODE 2011 –2015 (Prospect : Jurnal Manajemen dan Akuntansi, 2018)
This study aims to determine the effect of return on equity (ROE) and current ratio (CR ) to dividend payout ratio (DPR). This study uses data analysis methods, multiple regression, coefficient of determination t test and F test. Based on the results of research that researchers do by using SPSS program shows that the correlation test results between ROE variables with House of the amount of - 0.947, while the correlation test results between CR variables with House of equal to - 0.252. In the coefficient of determination obtained results of 0.796 which means that the contribution of ROE and C R variables to the variable of the House is 79.6%, while the remaining 20.4% is explained by other factors not examined in this study. In t test result for ROE variable obtained t count equal to - 4,044, because t count value of ROE smaller than t table (-4,044 <-4,303) hence Ho accepted and H1 rejected so that partially no influence between ROE variable to DPR. While the result of t test for CR variables obtained t count - 0.133, because t count smaller than t table (-0,133 <-4.303) then Ho accepted and H2 rejected sothat partially no influence between variable CR to variable DPR. In the f test results show that the value of f arithmetic of 8.799, because the value of farithmetic smaller than f table (8.799 <19.00) then Ho accepted and H3 rejected,so there is no effect simultaneously between the variables ROE and CR to DPR variables